(untitled) (Revista Contexto & Saúde, 2026)
Objective: To analyze the institutional context of the Primary and Specialized Healthcare Network in the healthcare of women with Human Immunodeficiency Virus (HIV). Method: This qualitative participatory research was conducted with 11 healthcare professionals and managers from municipal and federal healthcare services in a municipality in southern Brazil. Data were collected through focus groups and participant observation. The data were triangulated for analysis, and the discussion was mediated by interpretation in light of Institutional Ethnography. Results: The results were based on the discursive constructions of professionals and managers, and their observation notes. Three categories were then created: (1) trivialization of HIV infection and devaluation of women’s health needs, (2) institutional routines versus the needs of these women, and (3) disarticulation of the Primary and Specialized Healthcare Network. Conclusion: Healthcare is shaped, organized, and institutionalized under the influence of healthcare professionals’ understanding of HIV, and it appears to meet the demands of local services in a disjointed way, different from what these women need.